SYSTEMATIC PRODUCTION MANAGEMENT OF KEMBANG ATI PROGRAM ON MADU TV - Mohammad Rofiuddin; Reiza Praselanova; Muhammad Taufikurahman (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
Abstract Kembang Ati is a spiritual siraman program by ustadz and leading scholars in Kediri to open people's insights about religion, which is packaged interactively, with studio audiences and viewers at home that will make the da'wah atmosphere feel fluid and entertaining. In the program, a good production process is certainly needed in producing a quality program, therefore it takes a process that is full of preparation and careful and directed planning so that it can produce quality impressions. What is the series of production processes for the Kembang Ati program on Madu Tv? What are the supporting factors and inhibiting factors in the production process of the Kembang Ati program on Madu Tv? The type of research in this research is field research. The goal is to describe and express (to describe and explore).